Silviu Neguț, a Human Brand and a Social Phenomenon - Marius-Cristian Neacșu (Amfiteatru Economic)
Silviu Neguț (b. 1945), “a man not great in height”..., but great, very great in achievement, if we were to paraphrase the “old chronicler”, has accomplished more and more than anyone could imagine, knowing or seeing him. He had two successive careers of over a quarter of a century each, one as editor/editor-in-chief at Encyclopaedic/Scientific and Encyclopaedic Publishing House (1968-1993), followed by another teaching career in university education (1991-present) at the Academy of Economic Studies in Bucharest (“ASE”, as it is known to the entire country), graduating the University of Bucharest, as a geographer, but teaching geography and geopolitics for economists. These were doubled by two other careers run in parallel, one of soul, informal, as long as a lifetime, and that of publicist, enriching the spiritual life and the publishing market in Romania with several good meters of bookstore/library shelf (first title in 1972, first book in 1975 and he still writes today, accumulating dozens of specialized books, treatises, reference encyclopedias, school textbooks and university courses, hundreds of articles, etc.), with a talented style, clear, easy to understand, scientific, encyclopaedic and with literary overtones, as fluent as a river, without any gaps and without tiring the reader, on the contrary, making him feel awkward and regretful that the book is finished, and another, a fourth, managerial, being consecutively scientific secretary (1991-1993), vice-dean (1993-2008) and dean (a four-year term, 2008-2012) of the Faculty of International Business and Economics, after 2012 becoming emeritus professor at the Faculty of Commerce (now, Business and Tourism), where he still works today